Immobilization-induced symptomatic hypercalcemia treated with zoledronate in a child with a left ventricular assist device - Emrah Gün; Tanıl Kendirli; Edin Botan; Tayfun Uçar; Zehra Aycan; Ahmet Rüçhan Akar (Korean Society of Pediatric Endocrinology, 2021)
Differential diagnosis of hypercalcemia in children includes confirmation of hyperthyroidism, infection, inflammatory processes, and malignant tumors. Immobilization-induced hypercalcemia is rare in healthy individuals, although it can occur in adolescent males, especially after fracture. Immobility can cause increased skeletal calcium release and hypercalcemia, and this condition is also known as resorptive hypercalcemia. We present a case of a 10-year-old adolescent girl with advanced heart failure who underwent implantation with a HeartMate 3 left ventricular assist device. She had symptoms of abdominal pain, vomiting, and constipation on the fifth month of hospitalization. She subsequently developed immobilization-induced symptomatic hypercalcemia (serum calcium, 12.1 mg/dL; corrected calcium 12.8 mg/dL; parathormone, 1.9 pg/mL; calcium/creatinine ratio in spot urine, 1.21). However, hypercalcemia is uncommon in children with advanced heart failure. Bisphosphonate therapy was initiated because our patient did not respond to hydration and furosemide treatment, and she had persistent abdominal pain, vomiting, and constipation. The patient's complaints were resolved on the second day after administrating bisphosphonate, and hypercalcemia did not recur.